Unresponsiveness to Miltefosine in Visceral Leishmaniasis (VL) - An Experience of Seven Cases - Arif, Syed Md; Haque, Mirza Azizul; Choudhury, Ahmed Murtaza; Ahmed, Habib (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3329/jom.v9i2.1440 J MEDICINE 2008; 9 : 105-107